Post-traumatic cubitus varus: long-term follow-up of corrective osteotomy using the Ilizarov method of compression distraction osteogenesis. Issue 1 (18th December 2020) - Agrawal, Rajat; Agrawal, Ram Avtar; Kaul, Rajiv; Akhoon, Neha; Bollabathini, Raju
Abstract : The term cubitus varus describes the inward inclination of the supinated forearm on the extended elbow. The deformity manifests clinically as a decreased carrying angle, decreased range of motion (ROM) along with a cosmetically unsightly appearance. The aim of the present study was to evaluate the technique of compression-distraction osteogenesis using the Ilizarov apparatus in the management of patients with post-traumatic cubitus varus deformity. The objectives were to study the impact of this method on the ROM, the Humerus Elbow Wrist (HEW) angle as well as the Lateral Prominence Index. A total of 32 patients who presented with a cubitus varus deformity of ≥10° at the elbow were retrospectively analyzed using data retrieved from a computerized hospital database. All patients had undergone a mini-incision subperiosteal osteotomy followed by application of an Ilizarov frame. Cinico-radiological follow-up was carried out at regular intervals until union was achieved and yearly thereafter. The mean time to union was 11 weeks. The mean follow-up period ranged from 2 to 12 years (mean 4.0 years). Results were graded as excellent in 25 cases (78.1%), good in 2 (6.3%) and poor in 5 case (15.6%) using the grading system of Oppenheim. The mean HEW angle at final follow-up improved from 20° of varus to 6° of valgus. The mean flexion/extension improved from 121°/−3° preoperatively to 125°/−4° at final follow-up. The Mayo Elbow Performance scores at final follow-up were excellent in 23 cases, good in 7 and fair in 2. Complications encountered included superficial pintract infections in three cases, lateral condylar prominence in one case, loss of terminal flexion in three cases and valgus over-correction in one case.